Knowledge Transfers from Multinational to Domestic Firms: Evidence from Worker Mobility - Poole, Jennifer P. (The Review of Economics and Statistics, 2013)
Labor turnover is a commonly cited mechanism for the transmission of technology from multinational to domestic firms. Using a matched establishment-worker database from Brazil, I present evidence consistent with positive multinational wage spillovers through worker mobility. When workers leave multinationals and are rehired at domestic establishments, continuing-workers' wages increase. To my knowledge, this avenue for wage spillovers has not previously been explored. The paper also investigates where spillovers occur and how they are absorbed to demonstrate heterogeneous impacts. Higher-skilled former multinational workers are better able to transfer information, and higher-skilled incumbent domestic workers are better able to absorb information.